Studies on the Homalomeneae (Araceae) of Borneo XXV–A remarkable new kerangas-associated Homalomena[Chamaecladon Clade] from Sabah - Wong, Sin Yeng; Joling, Jyloerica; Boyce, Peter C. (Wiley-VCH GmbH, 2020)
Homalomena portae-inferniis described and illustrated as a new species of the Chamae-cladon Clade with scintillating-velutinous foliage restricted to lowland kerangas, and com-pared with the three morphologically most similar species on Borneo, and with the singleother Chamaecladon species described from the Tawau Hills National Park.